Contributions to the ethnology of the Haida. Memoirs of the AMNH - Swanton, John Reed, 1873-1958. (Leiden, E. J. Brill; New York, G. E. Stechert, 1905)
300 p. illus., XXVI pl., fold. maps, fold. geneal. tab. 36 cm.